Road traffic control by using Li-Fi Technology between Vehicle to Vehicle Communication - kumari, D.Raghava; Anitha , M.; rani, G.Jhansi; Babu, D. Ramesh (International Journal of Psychosocial Rehabilitation, 2020)
Road traffic control is biggest task which ever we face. Vehicle to vehicle communication is a new design to control the road traffic. This design is done by using a technology called Light-Fidelity (Li-Fi). It is a wireless technology which transmits the data via illumination. In our project we enlist Light-Fidelity technology. In this technology data is transferred from one vehicle to other vehicle via light. This technology is helpful to reduce the accidents and defended driving. Li-Fi uses visible light spectrum for transmission of data which is 10,000 times more than Wi-Fi spectrum. The transmission of data can be any type like text, audio or video. Transmission section comprises of LED which transfers light with the help of ultrasonic sensor to the receiver. Receiver section contains solar panel to perceive the original signal. When receiver will receive the signals from transmitter, then speed will be displayed on the LCD and motor will be controlled.